Efisiensi Pasar Valuta Asing di Indonesia - Juliana (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
The purpose of this research is to identify the efficiency validity of the weak and semi-strong form of foreign exchange market in Indonesia. The study use monthly data from exchange rate of six foreign currencies (Canadian Dollar, Swiss Franc, Euro, Pound Sterling, Japanese Yen and US Dollar) to Rupiah for the period January 2009 – December 2018. The efficiency of the weak form of the foreign exchange market is tested using units root test (Augmented Dickey Fuller and Phillips Perron), while semi-strong form efficiency was tested using Johansen cointegration. The unit root results show that the six currencies behave randomly so that they are consistent with the weak form of efficiency and the Johansen cointegration test shows that there is a long-term relationship between currencies which indicates that the market is not efficient in the semi-strong form.